Contesting syari'ah in the feed: Gender performativity, haram profit, and moral crisis among Acehnese digital celebrities - Nurdin, Hanifah; Kholil, Syukur; Indra, Farhan (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
The purpose of this study is to examine the controversy surrounding content produced by feminine male Instagram celebrities in Aceh, being perceived to conflict with the region's cultural and religious values. These influencers create content by dressing in women's clothing, using feminine accessories, and adopting female speech patterns. Despite this, their endorsements are widely used by businesses in Aceh, including by a local university. This shows that the feminine brand they have cultivated has successfully attracted an audience, even though the content itself contradicts established cultural and religious values. The content is fully commodified to gain financial profit. The method used in this research was virtual ethnography with four levels of data analysis: media space, media documents, media objects, and experiences. Additional data were obtained through interviews with two cultural figures and two religious leaders to strengthen the findings. The results of the study indicated that the content uploaded by these feminine male celebrities undermines Acehnese cultural values and violates Islamic religious values. The content shows a shift in original gender roles from male to female. This phenomenon of feminine male content is considered an identity crisis among Instagram celebrities, who can influence others through the content they produce. From a religious perspective, this content can damage the foundation of life, as seen in the Hadith of the Prophet Muhammad that prohibits men from dressing and appearing as women. Furthermore, the financial profits obtained are considered haram (unlawful) because the process of earning the money is not permitted by Islam.